HUBUNGAN DAYA LEDAK OTOT TUNGKAI (STANDING BROAD JUMP) DAN KEKUATAN OTOT PERUT DENGAN PRESTASI LOMPAT JAUH PADA SISWA PUTRA KELAS X MA AL-IHSAN NW GELONDONG KECAMATAN KOPANG KABUPATEN LOMBOK TENGAH - Hendri Saputra; Intan Primayanti (Universitas Pendidikan Mandalika, 2018)
The development of athletic yet not so good in particularly at central Lombok. Long jump achievement more or less influenced by certain factors, especially on the physical condition of the limb muscle and abdominal muscle, therefore need to be more in exercises. Based on the background, the research problem as follows; Is there any correlation of the limb explosive muscle power (standing broad jump) and the abdominal muscle power to the long jump achievement on the grade X male students of MA AL-IHSAN NW Gelondong Kopang in Central Lombok of 2016/2017 academic year. The purpose of this study is to find out whether there is correlation of the limb explosive muscle power (standing broad jump) and the abdominal muscle power to the long jump achievement on the grade X male students of MA AL-IHSAN NW Gelondong Kopang in Central Lombok of 2016/2017 academic year. The research result is analyzed by using the correlation formula of product moment. It shows that the r-score < r-table, that is 0.888 and 0.187 < 0602, while the total sample is 12 students on the significance level of 5%. It indicates that the rxy of null hypothesis (Ho) which says there is no correlation of the limb explosive muscle power (standing broad jump) and the abdominal muscle power to the long jump achievement on the grade X male students of MA AL-IHSAN NW Gelondong Kopang in Central Lombok of 2016/2017 academic year is rejected. In other words, there is correlation of the limb explosive muscle power (standing broad jump) and the abdominal muscle power to the long jump achievement on the grade X male students of MA AL-IHSAN NW Gelondong Kopang in Central Lombok of 2016/2017 academic year.